2009
DOI: 10.1007/978-3-642-04380-2_26
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Ice in Human-Agent Communication: Eye-Gaze Based Initiation of Contact with an Embodied Conversational Agent

Abstract: Abstract. In human-human conversation, the first impression decides whether two people feel attracted by each other and whether contact between them will be continued or not. Starting from psychological work on flirting, we implemented an eye-gaze based model of interaction to investigate whether flirting tactics help improve first encounters between a human and an agent. Unlike earlier work, we concentrate on a very early phase of human-agent conversation (the initiation of contact) and investigate which non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…[Krämer et al 2013] found that increases in character smiling increased smiling in viewers (but did not change the viewer's opinion of the avatar). [Bee et al 2009] studied whether flirting could improve first impressions between a user and a virtual character.…”
Section: Related Workmentioning
confidence: 99%
“…[Krämer et al 2013] found that increases in character smiling increased smiling in viewers (but did not change the viewer's opinion of the avatar). [Bee et al 2009] studied whether flirting could improve first impressions between a user and a virtual character.…”
Section: Related Workmentioning
confidence: 99%
“…A group of robots can display a variety of social behaviors that are impossible to convey in isolation, such as social intelligence, behavior coordination among individuals, and shared goal pursuit. These features may all affect observers' own social perceptions of the robots-for instance, causing them to like robots more (e.g., if they appear socially competent) [7,8].…”
Section: Proposed Explanationsmentioning
confidence: 99%
“…Many important social psychological factors that determine the quality and quantity of social interactions have been successfully applied to HRI research (e,g., gaze [7,8]). Less frequently applied, however, are social psychological theories that predict changes in these social factors when exposed to or interacting with groups versus individuals [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…From the virtual characters usually exposed in kiosks at museums and airports, to the latest technologies used in installations * e-mail:diana.arellano@filmakademie.de † e-mail:volker.helzle@filmakademie.de where the user embodies an avatar and sees the world through its eyes, human-computer interaction, or HCI has undergone a large number of improvements. The numerous researches in this area have intended to achieve more natural and better interaction, obtaining successful results as in the case of Eva, a virtual geography teacher [Kasap et al 2009]; the interactive football experts and moderator for the World Cup in Germany 2006 [Reithinger et al 2006]; Max, the virtual museum guide who is in permanent exhibition at the Heinz Nixdorf MuseumsForum since 2004 [Pfeiffer et al 2011]; and some other characters that have been used in more psychological and user experience experiments like MARC [Courgeon et al 2009], Greta [Niewiadomski et al 2009] or Alfred [Bee et al 2009]. …”
Section: Introductionmentioning
confidence: 99%